Design, synthesis and theoretical simulations of novel spiroindane-based enamines as p-type semiconductors - Sarune Daskeviciute-Geguziene; Maryte Daskeviciene; Kristina Kantminienė; Vygintas Jankauskas; Egidijus Kamarauskas; Alytis Gruodis; Smagul Karazhanov; Vytautas Getautis (Royal Society Open Science, 2024)
The search for novel classes of hole-transporting materials (HTMs) is a very important task in advancing the commercialization of various photovoltaic devices. Meeting specific requirements, such as charge-carrier mobility, appropriate energy levels and thermal stability, is essential for determining the suitability of an HTM for a given application. In this work, two spirobisindane-based compounds, bearing terminating hole transporting enamine units, were strategically designed and synthesized using commercially available starting materials. The target compounds exhibit adequate thermal stability; they are amorphous and their glass-transition temperatures (>150°C) are high, which minimizes the probability of direct layer crystallization. V1476 stands out with the highest zero-field hole-drift mobility, approaching 1 × 10−5 cm2 V s−1. To assess the compatibility of the highest occupied molecular orbital energy levels of the spirobisindane-based HTMs in solar cells, the solid-state ionization potential (Ip) was measured by the electron photoemission in air of the thin-film method. The favourable morphological properties, energy levels and hole mobility in combination with a simple synthesis make V1476 and related compounds promising materials for HTM applications in antimony-based solar cells and triple-cation-based perovskite solar cells.